Interaksi Senyawa Phloroglucinol sebagai Terapi Inflamasi melalui penghambatan gen Cyclooxygenase-2 (COX-2) - Yohanes Bare (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2022)
Exploration of natural compounds is one of the projects in the context of curving disease, one of which is inflammatory therapy in the body, one of the natural ingredients used is Phloroglucinol which has anti-inflammatory properties but there is no information on molecular studies related to its activity. The purpose of this study was to explore the potential of Phloroglucinol as an anti-inflammatory mechanism. Phloroglucinol compound (CID 359) was downloaded from the PubChem Protein COX-2 database (PDB ID 6cox) downloaded from the Protein Data Bank database. The compound Phloroglucinol interacted with the Molegro virtual Docker 5 program with Grid docking X 66,44; Y 27.44; Z 107.23. The docking results were analyzed using Discovery Studio software ver 21.1.1. The results showed that Phloroglucinol binds to five COX-2 amino acid residues and may inhibit COX-2 performance and can be a strong candidate for inflammatory therapy when inflammation occurs. in the human body. The conclusion of this study is that Phloroglucinol compounds have the potential in inhibiting COX-2 (inflammatory mediators).